Gelsolin expression in liver, spleen and blood plasma provides insights into its function in mice following acute insults. (December 2016) - Fu, Haiyan; Du, Hongyang; Hu, Zhansheng; Ying, Xiudong; Zhou, Rongbin
Background: Gelsolin (GSN) is an actin-binding plasma protein with a pivotal role in the systemic response to acute tissue damage. The present study investigated GSN expression in the liver, spleen and blood serum in mice after burn. Method: A murine model of thermal injury was selected, and the animals were sacrificed at 8, 24, 48 and 72 h after injury. Real-time quantitative polymerase chain reaction (RT-PCR) was performed to determine the messenger RNA (mRNA) expression of GSN, and GSN protein expression was determined by enzyme-linked immunosorbent assay (ELISA). Results: We found that GSN mRNA and protein were expressed in the liver, spleen and blood serum of the mice. GSN expression in these tissues was the lowest among the tested time points at 8 h after burn injury. The mortality within 72 h among the mice subjected to burn injury was significantly lower in those treated with GSN than in those not treated with GSN. Treatment with GSN markedly increased the GSN levels in the liver, spleen and blood serum after injury. Conclusion: These results indicated that GSN treatment may affect the outcome of thermal injury via changes in the GSN content of multiple tissues.